"Citādāks Reps" Vai "Kristīgā Glance": Dievs Un Pasaule Latvijas Kristīgajā Repā: "A Different Rap" or "Christian Groove": God and the world in Latvian Christian Rap. - Andrejevs, Ņikita (Cel̜š, 2022)
Historically, Christian rap emerged in the context of Evangelical Christianity in the US. Since its birth in the 1970s, it has been often represented as a tool for evangelization and outreach in the modern urban environment. Although there are stories of purported success of these attempts, most US Christian rappers have since turned to Christians as their primary audiences. There are two main attitudes towards the world and its culture among Christian rappers that are manifest in their approach to the style of their songs. Nevertheless, the general attitude towards the world and culture in Christian rap is that of distancing from these aspects, and Christian rappers want to transform or educate the faithless society, Thereby denying the world its capacity to acquire genuine meaning and truth without Christian assistance. There is a discussion on terminology for engaging Christian rap from an academic perspective. Although some Christian rap scholars prefer to use a definition such as "Christians and hip-hop" to include all the possible interactions of Christians, rappers, and hip-hop culture, throughout the article the studied phenomenon is called "Christian rap" to distance the study of the actual rap lyrics and theology they contain from the analysis of hip-hop beats, breakdance, graffiti and/or other elements of hip-hop culture. This problem with definition mirrors the discussion common to the study of Contemporary Christian music genres, where there is debate on the question of criteria that can be employed to define "Christian music". Latvian Christian rap represents an array of attitudes towards the world. There are examples of "worship rap" or separational approach to Contemporary Christian music and examples of integrational approach. These two approaches represent different attitudes towards the world, although fundamentally all Latvian Christian rappers that are mentioned in the article distance themselves from the world and wish to enlighten it or reach the faithless with their appropriation of popular contemporary music. Latvian Christian rap is a marginal phenomenon because it struggles with acceptance in Christian circles as much as among non-Christians that are to be its main and desired audience. Rap and hip-hop are perceived to be connected to protest, violence, drugs and other things that are foreign to the image of Christianity in Latvia.